Building Rapport with Student-Athletes: A Survey of Counselor Strategies - Green, Kelly E.; Denson, Eric L. (My University, 1993)
The importance of rapport in counseling student-athletes is commonly accepted, but the process of developing rapport has received little attention. Members of the National Association of Academic Advisors for Athletics (N4A) completed a questionnaire about methods they believed were important and effective in building rapport with student-athletes. The Student-Athlete Rapport Survey (SARS) was developed to elicit responses from academic advisors and athletic counselors about the methods they use to build rapport. The survey was sent to 385 members of the N4A; 213 usable surveys were returned (55%). Respondents also descnbed the ways in which they enticed student-athletes to use the services offered. Results and implications for athletic counselors were discussed. The methods most frequently endorsed as "very effective" were those in which counselor/athlete contact was either encouraged or required. The most effective methods of developing rapport were inviting student-athletes into the counselor's office, requiring them to meet the counselor in the office, and the coaches' requiring student-athletes to meet with the counselor.
Keywords: N4A; rapport; academic support